Borderline resectable pancreatic cancer: a consensus statement by the International Study Group of Pancreatic Surgery (ISGPS) - Bockhorn, Maximilian; Uzunoglu, Faik G.; Adham, Mustapha; Imrie, Clem; Milicevic, Miroslav; Sandberg, Aken A.; Asbun, Horacio J.; Bassi, Claudio; Büchler, Markus W.; Charnley, Richard M.; Conlon, Kevin; Cruz, Laureano Fernandez; et al. (Surgery, 2014)
Background - This position statement was developed to expedite a consensus on definition and treatment for borderline resectable pancreatic ductal adenocarcinoma (BRPC) that would have worldwide acceptability. - Methods - An international panel of pancreatic surgeons from well-established, high-volume centers collaborated on a literature review and development of consensus on issues related to borderline resectable pancreatic cancer. - Results - The International Study Group of Pancreatic Surgery (ISGPS) supports the National Comprehensive Cancer Network criteria for the definition of BRPC. Current evidence supports operative exploration and resection in the case of involvement of the mesentericoportal venous axis; in addition, a new classification of extrahepatic mesentericoportal venous resections is proposed by the ISGPS. Suspicion of arterial involvement should lead to exploration to confirm the imaging-based findings. Formal arterial resections are not recommended; however, in exceptional circumstances, individual therapeutic approaches may be evaluated under experimental protocols. The ISGPS endorses the recommendations for specimen examination and the definition of an R1 resection (tumor within 1 mm from the margin) used by the British Royal College of Pathologists. Standard preoperative diagnostics for BRPC may include: (1) serum levels of CA19-9, because CA19-9 levels predict survival in large retrospective series; and also (2) the modified Glasgow Prognostic Score and the neutrophil/lymphocyte ratio because of the prognostic relevance of the systemic inflammatory response. Various regimens of neoadjuvant therapy are recommended only in the setting of prospective trials at high-volume centers. - Conclusion - Current evidence justifies portomesenteric venous resection in patients with BRPC. Basic definitions were identified, that are currently lacking but that are needed to obtain further evidence and improvement for this important patient subgroup. A consensus for each topic is given.
Gesehen am 18.08.2020